Shaggy Photoreceptors with Subfoveal Fluid Associated with a Distant Choroidal Melanoma - Ann Q. Tran; James A. Eadie; Michael M. Altaweel (Case Reports in Ophthalmological Medicine)
Purpose. To describe the enhanced depth imaging optical coherence tomography (EDI-OCT) findings in a patient with an extra macula choroidal melanoma before and after treatment. Methods. Observational case report. Results. A 45 year-old Caucasian male patient was referred to retina clinic for management of choroidal melanoma. Examination revealed a nasal choroidal melanoma while EDI-OCT illustrated subfoveal fluid pocket with elongated shaggy photoreceptors distant and separate from the tumor. The patient was treated with plaque brachytherapy and intravitreal bevacizumab. One week after plaque removal, there was a dramatic reduction in the shaggy photoreceptors. Conclusion. Choroidal melanomas have effects that are not localized to the area of the tumor. This loculated pocket of subretinal fluid and coinciding changes to photoreceptor morphology may be related to global changes in choroidal function or release of tumor related cytokines.